Late-onset Leber’s hereditary optic neuropathy and antiandrogens for prostate cancer: is there a causative link? - Amore, Giulia; Carbonelli, Michele; D’Angeli, Diego; Bonan, Luigi; Faustini-Fustini, Marco; Maresca, Alessandra; Carelli, Valerio; La Morgia, Chiara (Frontiers in Neurology, 2025)
IntroductionLeber’s hereditary optic neuropathy (LHON) is a maternally inherited condition due to mitochondrial DNA (mtDNA) mutations usually affecting young men within their thirties, while women seem protected by estrogens with a female-to-male ratio of 1:3. Late-onset cases (over 40 years of age) are usually associated to toxic exposure to tobacco smoke or drugs causing mitochondrial dysfunction.ResultsWe describe two cases of LHON remarkable for their late onset (> 60 years) in the absence of classic toxic factors. They were both affected by advanced prostate cancer and developed LHON after introduction of enzalutamide, an antagonist of androgens’ receptor, in association with leuprolide, a gonadotropin-releasing hormone (GnRH) analogue, used in the context of Androgen deprivation therapy (ADT). Both patients presented very low serum levels of gonadotropin, estrogens and androgens compatible with hormonotherapy. MtDNA copy number in our probands resulted significantly reduced (like other LHON affected cases), compared to age-matched LHON unaffected mutation carriers and controls.DiscussionThe role of hormones in LHON pathogenesis remains still debated. Recent evidence suggests a protective effect of estrogens in increasing mitochondrial biogenesis (and mtDNA copy number), partially explaining the gender bias of the disease, while the role of androgens is yet to be fully understood. Considering the effect of the ADT on circulating hormonal levels and their reciprocal interactions, we hypothesize that in a context of already low estrogens levels due to GnRH analogue, the block of androgens receptors by Leuprolide further imbalance the estrogens to androgens ratio and eventually trigger the disease.